Middle-East OBGYN graduate education (MOGGE) foundation practice guidelines: use of labor charts in management of labor. Practice guideline no. 04-O-21. (12th December 2022) - Shazly, Sherif A.; Shawki, Abdelrahman A.; Ahmed, Manar M.; Monib, Fatma A.; Radwan, Ahmad A.; Sedik, Ahmed S.; Said, Aliaa E.; Ali, Shimaa S.; Abouzeid, Mostafa H.; Sayed, Esraa G.; Nassr, Ahmed A.; Eltaweel, Nashwa A.; et al.
Abstract: Since the 50 s of the last century, labor charts have been proposed and appraised as a tool to diagnose labor abnormalities and guide decision-making. The partogram, the most widely adopted form of labor charts, has been endorsed by the world health organization (WHO) since 1994. Nevertheless, recent studies and systematic reviews did not support clinical significance of application of the WHO partogram. These results have led to further studies that investigate modifications to the structure of the partogram, or more recently, to reconstruct new labor charts to improve their clinical efficacy. This guideline appraises current evidence on use of labor charts in management of labor specially in low-resource settings.